CONTEMPORARY APPROACHES TO THE PREVENTION OF GESTATIONAL DIABETES: PHARMACOLOGICAL INTERVENTIONS AND DIETARY SUPPLEMENTS – A NARRATIVE REVIEW - Sparić, Radmila; Stojković, Marta; Babović, Ivana; Plešinac, Jovana; Pavlović, Natalija; Simanić, Sara; Plešinac, Snežana (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: Gestational diabetes mellitus (GDM) is one of the most common pregnancy complications and an important public health concern, with increasing prevalence driven by rising obesity and insulin resistance. This study aimed to review current evidence on preventive strategies for GDM, including lifestyle interventions, supplementation, and pharmacological approaches.Material and methods: A literature review was conducted using MEDLINE, Scopus, and PubMed databases for the period from 2000 to 2025. Peer-reviewed studies addressing GDM prevention were included, while studies focused exclusively on treatment of established GDM, animal studies, articles not available in full text, and those not published in English were excluded. Study selection was performed independently by two authors, and in cases of discrepancy, consensus was reached among all authors.Results: Elevated pre-pregnancy and gestational body mass index is the most important modifiable risk factor for GDM. Lifestyle interventions, including maintenance of normal body weight, a balanced diet, and regular physical activity, represent the most effective preventive strategy, with physical activity showing the greatest impact. Among supplements, myo-inositol shows potential to reduce GDM incidence and improve glycemic control, whereas evidence for vitamin D, probiotics, and omega-3 fatty acids remains inconsistent. Metformin may reduce GDM risk in high-risk populations, particularly in women with polycystic ovary syndrome, but findings are heterogeneous, and concerns remain regarding long-term offspring outcomes.Conclusion: Lifestyle modification and dietary regimen remain the cornerstone of GDM prevention. Pharmacological therapy and dietary supplements may have a potential role in high-risk groups; however, there is insufficient evidence to support their routine use. Further large-scale studies are needed to establish optimal prevention strategies.
Keywords: gestational diabetes mellitus; prevention; myo-inositol; metformin; dietary supplement